1995
DOI: 10.2307/2445689
|View full text |Cite
|
Sign up to set email alerts
|

C 3 Photosynthesis in the Gametophyte of the Epiphytic CAM Fern Pyrrosia longifolia (Polypodiaceae)

Abstract: Sporophytes of some epiphytic species in the fern genus Pyrrosia exhibit Crassulacean acid metabolism (CAM), generally considered to be a derived physiological response to xeric habitats. Because these species alternate between independent sporophytic and gametophytic generations yet only the sporophyte has been characterized physiologically, experiments were conducted to determine the photosynthetic pathways present in mature sporophytes, immature sporophytes, and gametophytes of Pyrrosia longifolia. Diurnal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In another case, although the gametophyte Wade1694 was identified as A. parvulum, it could be another case of an independent gametophyte of an unknown Antrophyum species due to the extent of its sequence variation. In congruence with previous studies, these observations imply that gametophytes have a greater tolerance for environmental stresses such as desiccation and low temperatures than do their counterpart sporophytes (Martin et al, 1995;Watkins et al, 2007;Farrar et al, 2008;Watkins and Cardelu ´s, 2012).…”
Section: Identification and Ecology Of Vittarioid Gametophytessupporting
confidence: 90%
“…In another case, although the gametophyte Wade1694 was identified as A. parvulum, it could be another case of an independent gametophyte of an unknown Antrophyum species due to the extent of its sequence variation. In congruence with previous studies, these observations imply that gametophytes have a greater tolerance for environmental stresses such as desiccation and low temperatures than do their counterpart sporophytes (Martin et al, 1995;Watkins et al, 2007;Farrar et al, 2008;Watkins and Cardelu ´s, 2012).…”
Section: Identification and Ecology Of Vittarioid Gametophytessupporting
confidence: 90%
“…Friend (1975) reported that the maximal photosynthetic rate of Cibotium glaucum at 25°C was 0.16 µmol CO 2 g -1 s -1 . Hagar and Freeberg (1980) and Martin et al (1995) reported that the rate of Todea barbara at 22°C was 0.03 µmol CO 2 g -1 s -1 and 0.057 µmol CO 2 g -1 s -1 for Pyrossia longifolia (these units are converted), respectively. The respiration rate was also reported by Hagar and Freeberg (1980) and Martin et al (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been carried out on the photosynthesis of mature fern sporophytes (Böhning & Burnside 1956;Maeda 1969;Friend 1975;Prange et al 1983Prange et al , 1984Nobel et al 1984;Bauer et al 1991); however, few studies have been performed on that of gametophytes and young sporophytes. Although, photosynthesis and respiration of gametophytes have been measured by Friend (1975), Hagar and Freeberg (1980) and Martin et al (1995), they carried out the measurements on only a certain stage of growth; therefore, changes in activities with increasing growth cannot be determined from their data. For example, Hagar and Freeberg (1980) measured photosynthesis of young sporophytes with six to eight leaves, and Martin et al (1995) compared the activity of young and mature sporophytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…f.) C. V. Morton have evolved the Crassulacean acid metabolism (CAM) photosynthetic pathway, a highly water‐efficient strategy to capturing and fixing carbon often seen in sporophytes of desert plant species (Cushman, 2001 ; Kluge and Ting, 2012 ). In 1995, Martin et al used an IRGA (in conjunction with other tools) to characterize the photosynthetic pathway of Pyrrosia longifolia gametophytes, and demonstrated that this species of fern transitions from C 3 photosynthesis in the gametophyte stage to CAM in the sporophyte stage (Martin et al, 1995 ). Many epiphytic fern species have been shown to exhibit CAM photosynthesis (Martin et al, 2005 ), yet the adaptive value of this transition in these species has not been well demonstrated and is ripe for experimentation.…”
Section: Physiologymentioning
confidence: 99%